Eksistensi Pura Purohita di Desa Unggahan Kecamatan Seririt Buleleng - I Made Hartaka; I Putu Ariyasa Darmawan; Ni Luh Putu Yuliani Dewi (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2022)
The temple is a sacred place to worship God with all His manifestations as well as a place to worship the holy spirits of the ancestors. The temple is also a center for religious, social and cultural activities based on Hinduism. Purohita Temple is located at Unggasan Village, Seririt District, Buleleng Bali. Purohito Temple carries the concept of Shiva-Buddhist worship which is very unique. Pura Purohita has one Siva Phallus which became the highest Shiva Lingga in the world which was included in the MURI list on April 10, 2015. The dedication of Purohita Temple is a special attraction to be studied further about the existence of Purohita Temple in Uploadan village, Seririt District, Buleleng Regency. The research uses qualitative descriptive research methods. Purohita Temple structurally consists of two pages, namely: jaba pisan and jeroan, while when viewed from the shape of the sacred building, it can be classified into several types, namely: Bebaturan, Padmasana, Gedong, and Lingga. The function of Purohita Temple: (1) Religious function where Purohita Temple functions as a means of increasing sradha and bhakti for the people, (2) The function of education as a medium of learning or informal cultural and spiritual education. (3) Economic Function which in the area of Pura Purohita is placed the palinggih Ratu Subandar by taking the form of a statue of Laughing Buddha which is believed to be the god of prosperity and happiness (4) Recreation function where Pura Purohita is one of the religious tourist attractions in the North Bali region. The maning of Siva Phaluss is as a central point of worship to facilitate concentration and unification with God.